Impacts of Adoption Strategies for International Financial Reporting Standards on Supply Chain Control, Fraud, and Accounting Quality: Global Insights - Suriyanti, Suriyanti; Sayuthi, Dwi Putri Ramadhani; Putri, Puji Sabriani (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2024)
The empirical literature delves into how different approaches to implementing International Financial Reporting Standards (IFRS) impact both Supply Chain Control and accounting quality. While some research focuses on the effects of IFRS modifications on accounting quality, limited attention has been given to the broader implications of IFRS enforcement strategies. This study fills that gap by examining the influence of various IFRS adoption strategies on accounting quality and exploring the role of Fraud control as a mediator in this relationship. Using a two-step system GMM estimator and data from 35 countries spanning 2019 to 2023, the research reveals significant correlations between different IFRS adoption strategies and accounting quality. Specifically, both enforcement and modification strategies show positive associations with accounting quality, particularly in terms of timely loss recognition. Moreover, the study demonstrates that Fraud control acts as a mediator between IFRS adoption strategies and accounting quality. This suggests that the effectiveness of IFRS implementation and modification strategies in enhancing accounting quality is contingent upon the level of Fraud control. Notably, improvements in accounting quality are more pronounced when Fraud is effectively managed alongside IFRS implementation efforts. Overall, these findings underscore the importance of considering diverse IFRS adoption strategies and the role of Fraud control in enhancing accounting quality. By shedding light on these dynamics, the study contributes valuable insights to stakeholders and advances the understanding of accounting quality within the context of IFRS adoption.